Evidência sobre o conteúdo informacional da estrutura a termo da taxa de juros no Brasil : relação entre a ETTJ e a dinâmica econômica - Santos, Daiane Rodrigues dos (2011)
The work aims at identifying the relationship between the spread, difference of the long term interest rate in relation to the short term interest rate, and the economic dynamic. Specifically, it studies how the spread has impacted on the gross domestic product real growth rate, phenomenon pointed out by authors such as Harvey (1988), Sims (1972), Bernard & Gerlach (1996) and Estrella (2004), among others. It was verified, in the model VAR (6), that the Brazilian industrial production is weakly influenced by the spread. However, it was observed that the last one is strongly determined through the industrial production. This result is not found in the adopted theoretic approach. Additionally, it was verified that the spread is highly determined from the IPCA, which is, in its turn, strongly influenced through the spread, confirming the relations showed in Sims (1972), Shousha (2006), Nielsen (2006), among others. In the statistics of the dynamic model, VAR (6), it also presented an expressive effect from the industrial production on the IPCA, which, by contrast, is not significantly determining the industrial activity in the sample period.